Contraceptive use and its associated factors in Nigeria: Evidence from during and after COVID-19 - Timothy Samson; Adefunke Omoyajowo; Olumide Adeleke (Babcock University Medical Journal, 2025)
Objective: The COVID-19 lockdown widened the unmet contraceptive need with far-reaching implications for contraception methods and usage beyond the lockdown period. We set out to examine contraceptive use during and after the COVID-19 lockdown in Nigeria and its associated factors.